Inverter Practical Module Design for Power Electronics Course in Electrical Engineering Education Study Program - Suriani, Dewi; Fathiah, Fathiah; Ikhsan, Muhammad (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2024)
Inverter material is one of the essential materials in power electronics courses. An inverter is an electronic device that converts direct current (DC) into alternating current (AC). This concept is the foundation of electronics. Because the power electronics course is a practicum course, a practicum module is required as an intermediary teaching medium; this practical module discusses 3-phase inverter material, which uses the pulse width modulation (PWM) and sinusoidal pulse width modulation inverter (SPWM) switching methods. Through Tinkercad software, the circuit is assembled, and the output wave results from the two methods used are seen in designing the 3-phase inverter practical module using the Research and Development method. This research uses media and material validation sheet instruments to determine the feasibility of the 3-phase inverter practicum module. The research results showed that the percentage of media experts was 94%, material experts were 81%, and language experts were 84%. Hence, the 3-phase inverter practicum module is very suitable for use and can make it easier for students to understand inverters. Thus, developing a 3-phase inverter practicum module can effectively increase students' understanding of inverter material and interest in learning. It can also be an alternative for lecturers in teaching.